Plasmodium knowlesi Malaria in Humans and Macaques, Thailand - Jongwutiwes, Somchai (Centers for Disease Control and Prevention, 2011)
Naturally acquired human infections with Plasmodium knowlesi are endemic to Southeast Asia. To determine the prevalence of P. knowlesi malaria in malaria-endemic areas of Thailand, we analyzed genetic characteristics of P. knowlesi circulating among naturally infected macaques and humans. This study in 2008–2009 and retrospective analysis of malaria species in human blood samples obtained in 1996 from 1 of these areas showed that P. knowlesi accounted for 0.67% and 0.48% of human malaria cases, respectively, indicating that this simian parasite is not a newly emergent human pathogen in Thailand. Sequence analysis of the complete merozoite surface protein 1 gene of P. knowlesi from 10 human and 5 macaque blood samples showed considerable genetic diversity among isolates. The sequence from 1 patient was identical with that from a pig-tailed macaque living in the same locality, suggesting cross-transmission of P. knowlesi from naturally infected macaques to humans.